Microstructure and mechanical properties of fully sintered zirconia glazed with an experimental glass - Moreira Bastos Campos, Tiago; Marques de Melo Marinho, Renata [UNESP]; de Oliveira Pinto Ribeiro, Amanda [UNESP]; Larissa do Amaral Montanheiro, Thais; Carolina da Silva, Ana [UNESP]; Thim, Gilmar Patrocínio (Elsevier, 2021)
The need for improved mechanical properties in regions of higher masticatory loads led to the introduction of zirconia in dentistry. However, zirconia needs a characterization and glaze to have a more natural, tooth-like appearance. An experimental glass was produced based on the sol-gel method to exhibit a thermal expansion coefficient similar to that presented by zirconia. The experimental glass was used as glazing material on the previously sintered zirconia (vita YZ) surface. There was a significant reduction in the roughness and hardness of the material, caused by the formation of smooth, void-free and highly uniform glass coating. The glass infiltrated among superficial zirconia grains and caused the formation of monoclinic zirconia at the zirconia/glass interface. A consequent decrease in surface roughness and an increase in flexural strength and reliability was then observed in the experimental glass group. On the other hand, a significant decrease in the reliability of conventionally glazed group was observed. Therefore, the use of experimental glass instead of conventional glaze can improve the mechanical properties, smoothness, and mechanical reliability of fully sintered zirconia.
Keywords: Ceramics; Glaze; Interface; Strength; Weibull analysis